Doppler echocardiography in the study of patients with mitral disc valve prostheses. Issue 1 (January 1984) - Nitter-Hauge, S
Abstract : A combination of M mode and Doppler echocardiography was used to study patients with mitral disc valve prostheses. The probe used in these investigations consisted of a circular Doppler crystal mounted around the M mode crystal in the same plane. Because of the strong echoes produced by the prosthesis the transducer (probe) could be angled for optimum Doppler signals without losing the M mode echocardiographic recording of the prosthesis. With this equipment mean and maximum blood velocities and Doppler amplitude signals could be measured simultaneously with M mode echocardiography. A depth indication line in the M mode recording ensured that the Doppler signal was recorded in the region of interest. The Doppler ultrasound technique was also used separately in both the pulsed wave and the continuous wave mode. The data show the usefulness of this technique in patients with normally functioning valve prostheses and in three patients with valve malfunction due to thrombus formation. The data in the latter three cases seem to indicate that the Doppler technique provides valuable information in addition to that obtained by M mode echocardiography in recognising mitral valve prosthetic malfunction.